Health Literacy Requires Empowerment – Results of an Analysis of Patient Needs and the Demand for Qualification over a 10-Year Period - Simoes, E.; Wallwiener, D.; Kusicka, H.; Brucker, S. (Geburtshilfe und Frauenheilkunde, 2013)
Patients are expected to be increasingly competent about health issues, and patient self-determination is on the rise. This makes it ever more necessary to provide high quality information which is increasingly being offered to patients at all levels of the healthcare system. One example of a regionally available information service offered to patients is the Womenʼs Academy, created 10 years ago, at the University Womenʼs Hospital Tübingen in association with the Institute for Womenʼs Health. The Womenʼs Academy also serves as a forum and an outreach hub for the (cancer) centres of the Womenʼs Hospital. The topics addressed include problematic areas in medicine and problems in coping with health and disease and additionally reflect the emergence of various patient interests and needs over time. The communication between physician and patient is central to the promotion of health literacy and individualised medicine. Regionally available services like the Womenʼs Academy offer complementary benefits and are able to reach vulnerable groups of women who have little or no access to online information.
Keywords: gynaecology; health literacy; Womenʼs Academy; outreach